2016
DOI: 10.1039/c5cp06079f
|View full text |Cite
|
Sign up to set email alerts
|

PNIPAmx–PPO36–PNIPAmx thermo-sensitive triblock copolymers: chain conformation and adsorption behavior on a hydrophobic gold surface

Abstract: The chain conformations and adsorption behaviors of four thermo-sensitive poly(N-isopropylacrylamide)x-poly(propylene oxide)36-poly(N-isopropylacrylamide)x (PNIPAmx-PPO36-PNIPAmx) triblock copolymers with x values of 15, 33, 75, and 117 in dilute aqueous solutions were investigated by combined techniques of micro-differential scanning calorimetry (micro-DSC), static and dynamic light scattering (SLS & DLS), and the quartz crystal microbalance (QCM). PNIPAm15-PPO36-PNIPAm15 only exhibited the lower critical sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…[18][19][20] In principle, this type of technique can detect the adsorption, conformation and interactions of macromolecules at an interface. [21][22][23] For instance, Du and colleagues 24,25 investigated the adsorption of block copolymers on a gold (Au) surface using a QCM technique. The results indicated that the adsorption mechanism of a PNIPAm x -P123-PNIPAm x pentablock terpolymer was mainly determined by the interactions between the pentablock terpolymers molecules with different chain conformations in dilute aqueous solutions at various temperatures and the Au substrates with surface wetting and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In principle, this type of technique can detect the adsorption, conformation and interactions of macromolecules at an interface. [21][22][23] For instance, Du and colleagues 24,25 investigated the adsorption of block copolymers on a gold (Au) surface using a QCM technique. The results indicated that the adsorption mechanism of a PNIPAm x -P123-PNIPAm x pentablock terpolymer was mainly determined by the interactions between the pentablock terpolymers molecules with different chain conformations in dilute aqueous solutions at various temperatures and the Au substrates with surface wetting and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…2-Bromoisobutyrylbromide (BIBB, Sigma-Aldrich, 98%) was used as received. PPO- b -PNIPAm was synthesized according to the literature . Briefly, the macroinitiator was synthesized by the esterification of PPO-OH with BIBB.…”
Section: Methodsmentioning
confidence: 99%
“…PPO-b-PNIPAm was synthesized according to the literature. 41 Briefly, the macroinitiator was synthesized by the esterification of PPO-OH with BIBB. Through a standard ATRP procedure, the diblock copolymers with different degrees of polymerization of PNIPAm were synthesized.…”
Section: ■ Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations